MODELING PROBABLE PRECIPITATION FOR SOYBEAN IRRIGATION IN THE CERRADO OF MINAS GERAIS USING THE GAMMA DISTRIBUTION (REMUNOM, 2026)
This study evaluated the probable precipitation in Arinos-MG, a region characterized by tropical savanna climate, through statistical modeling with a gamma distribution applied to pluviometric series from 1991 to 2019. Data gaps were filled using the CLIMABR software, ensuring data integrity. Distribution parameters were estimated via maximum likelihood, employing specific functions to calculate probable precipitation percentiles (P60 to P90). Results indicated high seasonal variability: the average annual precipitation was approximately 1170.8 mm, with 86% concentrated between November and March. Probable precipitation percentiles varied monthly, with P60 ranging from 11.4 to 37.0 mm, P75 from 38.9 to 136.0 mm, and P90 from 158.6 to 547.2 mm. The average monthly effective precipitation reached 115.6 mm in January and dropped to 16.3 mm in November, indicating critical periods of water deficit for soybean cultivation. Monthly potential evapotranspiration ranged from 112 to 148 mm, reinforcing the need for supplemental irrigation, which reached up to 113.7 mm in months with lower natural water availability. The use of intermediate percentiles effectively balances water security and irrigation cost. It is concluded that the joint application of precipitation statistics and water balance is effective for rational planning of supplemental irrigation in the Cerrado Mineiro, promoting sustainability and agricultural productivity amid regional climate variability.